An examination of CBCT results for ectopic cuspid impaction: a case report - Manja, Cek Dara (Ikatan Radiologi Kedokteran Gigi Indonesia, 2026)
Objectives: This case report aims to examine the image of an ectopic canine impaction using cone beam computed tomography (CBCT). Case Report: A 23-year-old man came to our hospital with complaints of irregular, spaced teeth and a protruding sensation in his gums. There was no history of systemic disease. CBCT examination was performed. Multiplanar reconstruction showed the position of the impacted canine tooth with the crown facing labially and the root facing palatally. The position of the canine tooth caused the crown and root to penetrate the buccal and palatal cortical bone surfaces. Conclusion: CBCT 3D effectively assesses the position of the impacted canine tooth, including its crown and root, and evaluates its relationship with surrounding structures. This assessment is crucial for determining treatment prognosis, as conventional radiography may misinterpret the tooth's position.